Vermicomposting of food waste - Othman, Norzila (International Journal of Integrated Engineering, 2012)
The use of food waste recycling concept can be an interesting option to reduce the use of landfill. This strategy is more environmental friendly, cheap and fast if proper management to treat the food waste is applied. Nowadays, the concept of recycling is not well practice among the community. In this study, vermicomposting is introduced as an alternative of the food waste recycling. Vermicomposting consists of the use of earthworms to break down the food waste. In this vermicomposting treatment, the nightcrawler earthworm are used to treat the food waste. The food will be collected from UTHM cafe. The experiment consist of peat soil as a base, earthworms and the food waste. The pH number and moisture content of each container were controlled at 7.0 to 7.2 and 60 to 80 % to maintain the favorable environment condition for the earthworms. The weight of the sample will be measured in three days time after exposure to the earthworm. The vermicomposting study was taken about two weeks time. After the treatment, the soil sample are tested for nitrogen (N), Phosphorus (P), and Potassium (K) concentration. Based on the result obtained, it shows that vermicomposting will reduce the weight of treatment sample and the concentration of N, P, and K for the soil is greater than the chemical fertilizer. Therefore, vermicomposting is a promising alternative treatment of food waste as it is more ecofriendly.